The Role of Dll4/Notch Signaling in Normal and Pathological Ocular Angiogenesis: Dll4 Controls Blood Vessel Sprouting and Vessel Remodeling in Normal and Pathological Conditions - Ivan Lobov; Natalia Mikhailova (Journal of Ophthalmology, 2018)
Background. Retina is the highest oxygen-demanding and vascularized tissue in the body. Retinal development and function require proper vascularization and blood vessel function and integrity. Dll4 is most prominently expressed in the endothelium of angiogenic blood vessels and in quiescent arteries and capillaries in all tissues and organs of the mammalian species, and it is the key regulator of blood vessel sprouting. Results. Dll4 is a transmembrane protein that acts as a ligand for Notch receptors 1 and 4. Genetic deletion of Dll4 causes severe abnormalities in embryonic and postnatal vascular development. Deletion of even a single Dll4 allele results in almost complete embryonic lethality due to severe vascular abnormalities, the phenomenon called haploinsufficiency indicating the critical role of Dll4/Notch in vascular development. Dll4/Notch pathway interplays at multiple levels with other signaling pathways including VEGF, Wnt/Fzd, and genes controlling vascular toning. Multiple studies of the effects of Dll4 inhibition were performed in the developing retina to elucidate the key functions of Dll4 in normal and pathological angiogenesis. Several genetic approaches and therapeutic molecules were tested to evaluate the biological and therapeutic effects of acute and prolonged Dll4 inhibition in the eye and oncology. Conclusions. All current studies demonstrated that Dll4 controls blood vessel sprouting, growth, and remodeling in normal and pathological conditions as well as arterial-venous differentiation. Genetic and therapeutic Dll4 modulation studies show that Dll4 inhibition can promote blood vessel sprouting and might be useful to stimulate vessel growth in the ischemic retina and Dll4 is the key modulator of the postangiogenic vascular remodeling that ultimately defines vascular patterning.